Homeland Security: Establishment and Implementation of the United States Northern Command - Bowman, Steven R. (Library of Congress. Congressional Research Service., 2006)
This report discusses the U.S. Northern Command (NORTHCOM), which was established by the Department of Defense (DOD) to fight terrorism at home. Significant organizational and procedural progress has been made in setting up this organization. However, questions remain concerning interagency relationships and information sharing.